Evaluasi Perubahan Tata Guna Lahan sebagai Upaya Menjaga Kerbelanjutan Fungsi Waduk - Purboseno, Sentot (Department of Civil Engineering, Diponegoro University, 2013)
The increasing incidence of floods and droughts from year to year, indicating the destruction of water catchment areas. Opening of the forest to the wake region will be lead to increase floods and droughts in the downstream region, so the level of water availability has declined. Evaluation characteristics of the catchment area as a manufacturers producing surface water and groundwater needs to be done, to assess changes in the characteristics of the catchment area, towards the conservation of water resources can be focused and on target. Because it is associatednwith water results, then evaluation characteristics of the catchment area is done with the approach flow parameters in rainfall models. One of the popular models used rain flow, especially in the Java is FJ.Mock models, this model was developed from research in several watersheds in Java. From the research to changes in catchment characteristics with Mock model approach to Rawapening Reservoir catchment, from year to year decreased infiltration parameter values, whereas the direct flow increased. Refers to changes in the characteristics of the DTA, conservation activities to be done is to increase the infiltration capacity and reduce flow area directly. While the analysis of land use change, forest area declined from year to year and the areas of increased impermeable.